Formulation and Physicochemical Evaluation of Spray Gel Containing Cordyline fruticosa L. Leaf Extract for Topical Delivery - Alfina Nurrahman; Annora Rizky Amalia; Andany Oktamia Ningtyas Hartoyo (Natural Sciences Engineering and Technology Journal, 2024)
Spray gel is a gel system applied through a spray pump, producing small or large liquid droplets. Cordyline fruticosa (L.) A. Cheval, commonly known as Andong Merah, is a plant with various medicinal properties, including wound healing activity attributed to its flavonoid content. This research aimed to formulate and evaluate the physicochemical properties of a spray gel containing Cordyline fruticosa leaf extract for topical delivery, focusing on the effects of different concentrations of Carbopol 940 as a gelling agent and sorbitol as a humectant. Cordyline fruticosa leaf extract was obtained by maceration using 96% ethanol. Three spray gel formulations were prepared, varying the concentrations of Carbopol 940 (0.4 g, 0.6 g, and 0.8 g) and sorbitol (5 ml, 7.5 ml, and 10 ml). The prepared spray gels were then subjected to physicochemical evaluation, including organoleptic tests (color, odor, and consistency), homogeneity tests, pH measurements, viscosity measurements, spray pattern analysis, and adhesion tests. All spray gel formulations exhibited acceptable physicochemical properties. The formulations were homogeneous, with a pH within the acceptable range for topical applications. The viscosity and adhesion properties varied with the concentrations of Carbopol 940 and sorbitol. The spray pattern analysis revealed a circular spread pattern, with the pressure required for spraying influenced by the viscosity of the formulation. The spray gel formulations containing Cordyline fruticosa leaf extract demonstrated good physicochemical qualities, indicating their potential suitability for topical delivery. Further studies are recommended to optimize the formulation for enhanced stability and therapeutic efficacy.